DEVELOPMENT OF CANVA-BASED “LOVE TO READ” BIG BOOK MEDIA TO IMPROVE LITERACY SKILLS - Ulfa Yulianingsih; Noor Malihah (Al-Ibda: Jurnal Pendidikan Guru Madrasah Ibtidaiyah, 2023)
The method in this research is Research and Development (R&D) with the ADDIE model. The subjects of this research were teachers and students of class I at MI Tarbiyatul Islamiyah Noborejo. The research instruments used were interview guidelines, reading script instruments, pretest and posttest assessment guidelines, small group and large group trial sheets. The R&D stages are as follows: 1) analysis, 2) design; 3) develop; 4) implementation; and 5) Evaluation. The results of this research show that: 1) big book-based Canva media is an important media needed to support students in improving literacy skills. 2) the development of big book based Canva media was carried out through several stages a) the results of validation tests from material experts and media experts obtained an average score of 4.34 which means the big book is very suitable for use, b) then the effectiveness of the development of big book based Canva media was carried out through 2 trials, namely a small group trial with 6 students obtained an average score of 4.5 and a large group trial with 21 students obtained an average value of 4.32. Based on these trials, big book-based media is suitable for use. 3) The effectiveness test of big book based Canva media was analyzed by SPSS 28 and obtained a paired sample t-test of 11.939 which was greater than the t table of 2.080 with p=0.000<0.005. Thus, big book-based Canva media is effective in improving the literacy skills of class I students at MI Tariyatul Islamiyah Noborejo.